The Correspondence by Irina Obodovskaya and Mikhail Dementyev with Tatiana Tsiavlovskaya (Based on the Obodovskaya-Dementyev Archive at the Alexander Pushkin State Museum) - Tatiana B. Tishunina (Литературный факт, 2024)
The publication introduces into scholarly circulation the correspondence of prominent Pushkinists Mikhail Dementiev and Irina Obodovskaya, kept at the Alexander Pushkin State Museum. The central place in the correspondence is dedicated to the discussion of various ways to translate Alexander Pushkin’s letter to his brother-in-law Dmitry Goncharov. The letter which M. Dementiev and I. Obodovskaya found in Russian State Archive of Ancient Acts in 1970 was the result of their many years study of the Goncharov’s archive. The discovery of Pushkin’s genuine letter in the second half of the 20th century was a very important event: 4 pages of Pushkin’s text testify to the extremely difficult financial situation of the poet, in connection with which he was forced to turn to his brother-in-law with a request to borrow 6 thousand rubles for 6 months. This letter contains a constant theme of his correspondence in the 1830s: concern about the growing family, about the future of his children, about the impossibility to dedicate himself completely to poetry and writing and to make a living by literary works. The Pushkinists announced their discovery at the academic event held at the Alexander Pushkin State Museum. The publication presents memories of this evening, preserved by Alexander Krein, the first director of the museum. The article also observes other archival findings of M. Dementiev and I. Obodovskaya. M. Dementiev’s memoirs describing his meetings with an imminent literary and textual critic Tatiana Tsiavlovskaya are published for the first time.